Did we reach the 2005 targets for tuberculosis control? - Christopher Dye; Mehran Hosseini; Catherine Watt
The World Health Assembly set targets to detect by 2005 at least 70% of all new sputum smear-positive cases arising each year and to cure at least 85% of these cases. The national tuberculosis (TB) control programmes of 199 countries reported that in 2005, 2.3 million new smear-positive cases were diagnosed under WHO's DOTS strategy, out of an estimated 3.9 million (95% confidence limit (CL) 3.4 million to 4.4 million) new smear-positive cases arising in that year, a global case detection rate of 60% (95% CL 52% to 69%). Of 2.1 million new smear-positive patients registered for treatment in 2004, 84% had successful outcomes. Of the regions, only the WHO Western Pacific Region reached both targets, with case detection and treatment success rates of 76% and 91%, respectively; South-East Asia reached the treatment success target with a rate of 87%. In relation to countries, WHO estimates that 67 achieved the target detection rates and 57 achieved the target for treatment success, with 26 - including high-burden countries China, the Philippines and Viet Nam - achieving both targets. DOTS programmes diagnosed more than 26 million patients (all forms of TB) in 1995-2005. Building on this success, the Global Plan to Stop TB 2006-2015, describes the actions needed to implement WHO's new Stop TB Strategy over the coming decade to reduce TB incidence, prevalence and deaths in line with the Millennium Development Goals.